2019
DOI: 10.5194/tc-2018-288
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Two-dimensional Inversion of wideband spectral data from the Capacitively Coupled Resistivity method – First Applications in periglacial environments

Abstract: Abstract. The Capacitively Coupled Resistivity (CCR) method determines the electrical resistivity and permittivity by analysing the spectra of magnitude and phase shift of the electrical impedance. The CCR is well suited for the application in cryospheric and periglacial areas, because these areas provide the required physical conditions and logistical advantages of the method regarding the problems of coupling on highly resistive grounds and in some cases hard surfaces. Since the electrical properties of ice … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…A mathematical description of those effects can be achieved by a parametrization of the frequency-dependent permittivity. As discussed by Mudler et al (2019), a useful parameterization for 2-D inversion is the model suggested by Cole and Cole (1941) extended by a third term including the DC conduction for a comprehensive description of the electrical behaviour. This extended Cole-Cole model (in the following just named Cole-Cole model), which has been used previously for cryospheric investigations (e.g.…”
Section: Electrical Permittivity Of Frozen Soilmentioning
confidence: 99%
See 4 more Smart Citations
“…A mathematical description of those effects can be achieved by a parametrization of the frequency-dependent permittivity. As discussed by Mudler et al (2019), a useful parameterization for 2-D inversion is the model suggested by Cole and Cole (1941) extended by a third term including the DC conduction for a comprehensive description of the electrical behaviour. This extended Cole-Cole model (in the following just named Cole-Cole model), which has been used previously for cryospheric investigations (e.g.…”
Section: Electrical Permittivity Of Frozen Soilmentioning
confidence: 99%
“…The measured impedance spectra can be analysed either separately or in a two-dimensional inversion algorithm. Both procedures are described by Mudler et al (2019) and use the Cole-Cole model (Eq. 1) to fit the spectral data.…”
Section: Ice Content Estimationmentioning
confidence: 99%
See 3 more Smart Citations